2007
DOI: 10.1211/jpp.59.4.0008
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and enzymatic evaluation of 6-bridged imidazolyluracil derivatives as inhibitors of human thymidine phosphorylase

Abstract: A series of novel imidazolyluracil conjugates were rationally designed and synthesised to probe the active site constraints of the angiogenic enzyme, thymidine phosphorylase (TP, E.C. 2.4.2.4). The lead compound in the series, 15d, showed good binding in the active site of human TP with an inhibition in the low muM range. The absence of a methylene bridge between the uracil and the imidazolyl subunits (series 16) decreased potency (up to 3-fold). Modelling suggested that active site residues Arg202, Ser217 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The GRID analysis showed that C-6 of 5-chlorouracil (3) was desirable as the position of substituent introduction in order to improve inhibitory activity. The 6-substituted 5-chlorouracil derivatives (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) had some inhibitory activity, and compounds 21, 22, 25-27 having an imino group on the C-6 position had potent inhibitory activity. But the Cmax of compounds (21, 25, 27) among them was very low in comparison with that of compounds 18 and 20.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The GRID analysis showed that C-6 of 5-chlorouracil (3) was desirable as the position of substituent introduction in order to improve inhibitory activity. The 6-substituted 5-chlorouracil derivatives (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) had some inhibitory activity, and compounds 21, 22, 25-27 having an imino group on the C-6 position had potent inhibitory activity. But the Cmax of compounds (21, 25, 27) among them was very low in comparison with that of compounds 18 and 20.…”
Section: Resultsmentioning
confidence: 99%
“…It was estimated that the ammonium ion of site A, B and C made hydrogen bond with T118, S117 and phosphate, individually ( Figure 3). At first compounds (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were designed corresponding to the docking pose of model compound A using the calculated logP (CLOGP) and electron density of the nitrogen atom (Ncharge) as QSAR parameter ( Table 2). The CLOGP value of designed compounds (10-20) was calculated as logP by Bio-Loom for Windows [28].…”
Section: Lead Optimization By Docking Study and Qsar Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Highly lipophilic molecules will partition into the lipid interior of membranes and retain there. When log P is higher than the upper limit, the drug molecule will have low solubility whereas in lower log P, the drug has difficulty to penetrate the lipid membranes 33 . The pharmacokinetics results (Table 3) showed that all the compounds reported have good balance between compound solubility and its penetration of the lipid bilayers.…”
Section: In Vitro Cox Inhibitory Activitymentioning
confidence: 99%